2021
DOI: 10.1007/s10639-021-10492-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing students’ satisfaction with continuous use of learning management systems during the COVID-19 pandemic: An empirical study

Abstract: COVID-19 has impacted educational processes in most countries: some educational institutions have closed, while others, particularly in higher education, have converted to online learning systems, due to the advantages offered by information technologies. This study analyzes the critical factors influencing students’ satisfaction with their continuing use of online learning management systems in higher education during the COVID-19 pandemic. Through the integration of social cognitive theory, expectation confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 36 publications
10
62
1
6
Order By: Relevance
“…The likely cause for this is the training they received during the pandemic, and their perceived usefulness and satisfaction affirming the findings of Vanitha and Alathur ( 2021 ) that the perceived usefulness and satisfaction of learners in higher education improved the adoption of digital technologies for teaching and learning. Their plan to use digital artifacts in the future may also be influenced by personal outcome expectations, as these types of expectations significantly influence learners' continuous intention to use a digital artifact—learning management system (Alzahrani & Seth, 2021 ). This finding implies that blended learning (a new normal) will get normalised in university settings in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The likely cause for this is the training they received during the pandemic, and their perceived usefulness and satisfaction affirming the findings of Vanitha and Alathur ( 2021 ) that the perceived usefulness and satisfaction of learners in higher education improved the adoption of digital technologies for teaching and learning. Their plan to use digital artifacts in the future may also be influenced by personal outcome expectations, as these types of expectations significantly influence learners' continuous intention to use a digital artifact—learning management system (Alzahrani & Seth, 2021 ). This finding implies that blended learning (a new normal) will get normalised in university settings in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Using ICT in higher education has been increasingly common since the advent of the Internet, though the degree of its use differs from one context to another. A plethora of research claims that digital technology meets not only the changing need of higher education students, but it also enhances learning (Alzahrani & Seth, 2021 ; Becker, 2017 ; Du Toit & Verhoef, 2018 ; Lai, 2011 ; Laudari & Maher, 2019 ; Underwood, 2009 ; Waghid & Waghid, 2016 ). Lai ( 2011 ) and Underwood ( 2009 ), for example, assert that technology is used in all higher education institutions, though to varying degrees, to support traditional forms of teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cidral et al [20] integrated the D&M success model with the antecedents of e-learning satisfaction model of Sun et al [32] to investigate the usage of e-learning systems and its impact on the individual in Brazilian higher education. A recent study was conducted during the COVID-19 pandemic to investigate the effects of various factors on students' continuance intention to use LMSs in the UK, the study developed a conceptual framework based on the integration of the D&M success model, social cognitive theory, and expectation confirmation theory [33].…”
Section: B Theoretical Bases Of E-learning Research Modelmentioning
confidence: 99%
“…In online learning context, past research exploring the relationship between self-efficacy and satisfaction have primarily concentrated on the technical dimension of self-efficacy, such as Internet self-efficacy (Liang & Tsai, 2008;Kuo et al, 2014), computer self-efficacy (Jan, 2015;Johnson et al, 2008;Lim, 2001), and learning management system self-efficacy (Martinet al, 2010). However, in a recent study Alzahrani and Seth (2021) analyzed factors influencing students' satisfaction with their continuing use of online learning management systems in higher education during the COVID-19 pandemic. The findings revealed that self-efficacy had substantial effects on satisfaction.…”
Section: Introductionmentioning
confidence: 99%